Ambient Noise Data Processing to Obtain Group Velocity for Subsurface Structure Identification: Preliminary Research in Hululais Geothermal Field, Sumatra, Indonesia - Tavip Dwikorianto; Daud, Yunus; Agustya Adi Martha; Aditya A Juanda (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
Hululais area lies in the pull-apart basins of the Ketaun Segment and Musi Segment fault as a part of the Sumatra Fault Zone (SFZ). The boundary normal faults of pull-apart basins play an important role as major discharge zones for geothermal fluid because the extensional stress is concentrated in the boundary normal faults. In order to identify the geothermal reservoir structure in Hululais Geothermal Field (HGF), we introduce the local-scale study of the Rayleigh wave group velocity structure using ambient noise tomography (ANT). The ANT studies were collected using 18 seismometers inside 12 km2 area with a spacing of 125 – 500 meters, deployed across the fault structure for 1 month. More than two thousand Rayleigh Green’s Functions are extracted by cross-correlation at available station pairs. Using the estimated green function in this preliminary research, the group velocity as a function of the period can measure the dispersion curve by using multiple filter technique (MFT) and fast marching surface tomography (FMST) scheme to obtain group velocity images. The tomography result as group velocity image shows the subsurface Rayleigh wave structure variation. The NW-SE main structure is reflected by the contrast velocity structure between the central part and the north eastern-south western sides. The central part shows the low periods which are associated with low wave velocity However the margin of the central part shows the high velocity in all periods. The ANT studies have been efficient in time and cost, however useful in subsurface structure interpretation in Hululais Geothermal Field.